How the FMR1 gene became relevant to female fertility and reproductive medicine - Gleicher, Norbert; Kushnir, Vitaly A.; Weghofer, Andrea; Barad, David H. (Frontiers in Genetics, 2014)
This manuscript describes the 6-year evolution of our center’s research into ovarian functions of the FMR1 gene, which led to the identification of a new normal CGGn range of 26-34. This “new” normal range, in turn, led to definitions of different alleles (haplotypes) based on whether no, one or both alleles are within range. Specific alleles then were demonstrated to represent distinct ovarian aging patterns, suggesting an important FMR1 function in follicle recruitment and ovarian depletion of follicles. So called low alleles, characterized by CGGn<26, appear associated with most significant negative effects on reproductive success. Those include occult primary ovarian insufficiency (OPOI), characterized by prematurely elevated follicle stimulating hormone (FSH) and prematurely low anti-Müllerian hormone (AMH), and significantly reduced clinical pregnancy rates in association with in vitro fertilization (IVF) in comparison to women with normal (norm) and high (CGGn>34) alleles. Because low FMR1 alleles present in approximately 25% of all females, FMR1 testing at young ages may offer an opportunity for earlier diagnosis of OPOI than current practice allows. Earlier diagnosis of OPOI, in turn, would give young women the options of reassessing their reproductive schedules and/or pursue fertility preservation via oocyte cryopreservation when most effective.